Prospective study of comparison between the ultrasonography with the plain radiography in the diagnosis of pneumoperitoneum of hollow viscus perforation - Hebbar, Ashwin K.; T.M., Shashidhara; Iyanna, Harish; B.V., Sudhir; B.V., Sushil Kumar (International Journal of Research in Medical Sciences, 2017)
Background: This study was conducted to compare the plain radiography with the abdominal ultrasonography in the detection of pneumoperitoneum in suspected cases of hollow viscus perforation. Methods: A total number of 60 patients with suspected hollow viscus perforation were studied. All the patients had undergone plain radiography (Erect x-ray abdomen and left lateral decubitus views), ultrasonography and exploratory laparotomy. The investigational findings were compared with that of laparotomy findings. They were compared in terms of their sensitivity, specificity, predictive value of a positive and negative results and their percentage of false positive and false negative results. Results: Of the 60 patients, who underwent laparotomy, 57 had hollow viscus perforation. Out of 3 non-hollow viscus perforated cases 2 had appendicular perforation and 1 had mesenteric lymphadenitis. In the diagnosis, ultrasonography vs. radiography, their respective parameters were sensitivity (73.7% vs. 80.7%), specificity (66.7% each), predictive value of a positive test (97.7% vs. 97.9%), predictive value of a negative test (11.8% vs. 15.4%), percentage of false negative (26.3% vs. 19.3%) and percentage of false positive (33.3% each). Conclusion: In detection of pneumoperitoneum plain radiography appears to be more sensitive than ultrasonography with comparable specificity. Ultrasonographic finding of pneumoperitoneum is considered as an added finding.